2020
DOI: 10.3390/robotics9040079
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Long-Term Child–Robot Interaction on the Attention and the Engagement of Children with Autism

Abstract: Using a social robot has been proven to have multiple benefits for the training of children with Autism Spectrum Disorder (ASD). However, there is no clarity on the impact of the interaction quality between a child with ASD and a robot on the effectiveness of the therapy. Previous research showed that the use of a robot in Pivotal Response Treatment (PRT) could be an effective treatment component in diminishing ASD-related symptoms. Further analyzing the data from a randomized controlled trial of PRT treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Future studies will include comparison studies with typically developing children, with more advanced reinforcement learning algorithms and deep learning frameworks, and clinical evaluations in long term with our clinical collaborators. Long-term interaction and longitudinal analysis ( Clabaugh et al, 2018 ; Clabaugh et al, 2019 ; van Otterdijk et al, 2020 ) are very important topics in HRI, especially for the robots to function more effectively “in-the-wild” ( Park et al, 2020 ), and our future efforts plan to address these factors more dedication and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will include comparison studies with typically developing children, with more advanced reinforcement learning algorithms and deep learning frameworks, and clinical evaluations in long term with our clinical collaborators. Long-term interaction and longitudinal analysis ( Clabaugh et al, 2018 ; Clabaugh et al, 2019 ; van Otterdijk et al, 2020 ) are very important topics in HRI, especially for the robots to function more effectively “in-the-wild” ( Park et al, 2020 ), and our future efforts plan to address these factors more dedication and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasize the importance of parental involvement since it allows researchers to observe child behaviors outside the intervention and generalize improvements. Following this study, Otterdijk et al (2020) reported that children remained attentive and engaged with their parents throughout the multiple robot-assisted PRT sessions. In general, parents seem supportive of social robots and their application in autism therapy.…”
Section: Parents In Robot-assisted Autism Therapymentioning
confidence: 92%
“…От гледна точка на учещия обаче, богатството на субективния опит е много по-широко, включващо също така засилване на мотивационните фактори в ученето [напр. 5,6].…”
Section: нива или "слоеве" на достъпносттаunclassified